Consumer preferences for teledermoscopy screening to detect melanoma early. (January 2016) - Spinks, Jean; Janda, Monika; Soyer, H Peter; Whitty, Jennifer A
Introduction: 'Store and forward' teledermoscopy is a technology with potential advantages for melanoma screening. Any large-scale implementation of this technology is dependent on consumer acceptance. Aim: To investigate preferences for melanoma screening options compared with skin self-examination in adults considered to be at increased risk of developing skin cancer. Methods: A discrete choice experiment was completed by 35 consumers, all of whom had prior experience with the use of teledermoscopy, in Queensland, Australia. Participants made 12 choices between screening alternatives described by seven attributes including monetary cost. A mixed logit model was used to estimate the relative weights that consumers place on different aspects of screening, along with the marginal willingness to pay for teledermoscopy as opposed to screening at a clinic. Results: Overall, participants preferred screening/diagnosis by a health professional rather than skin self-examination. Key drivers of screening choice were for results to be reviewed by a dermatologist; a higher detection rate; fewer non-cancerous moles being removed in relation to every skin cancer detected; and less time spent away from usual activities. On average, participants were willing to pay AUD110 to have teledermoscopy with dermatologist review available to them as a screening option. Discussion and conclusions: Consumers preferentially value aspects of care that are more feasible with a teledermoscopy screening model, as compared with other skin cancer screening and diagnosis options. This study adds to previous literature in the area which has relied on the use of consumer satisfaction scales to assess the acceptability of teledermoscopy.